Wireless autonomic neural network in EEG signal extraction management. (1st January 2014) - Onunka, Chiemela; Bright, Glen; Stopforth, Riaan
The use of autonomic neural network in the control of smart machines using bio-signals has created the need for advancements in autonomic neural network in EEG signal extraction management. The advancements made in using human cognition for robotic control have increased possibilities once imagined in the field of robotics. The focus of the study is on the application of wireless autonomic neural network in EEG signal extraction. The paper discusses the importance of autonomic neural network in brainwave extraction, transmission and management for robotic control. The prediction and extraction process is an important component of the EEG autonomic neural network.